Psoriasis in children - Pinson R (Dove Medical Press, 2016)
Roxanne Pinson,1 Bahman Sotoodian,2 Loretta Fiorillo2,3 1School of Medicine, 2Division of Dermatology and Cutaneous Sciences, Department of Medicine, 3Division of Pediatric Dermatology, Department of Pediatrics, University of Alberta, Edmonton, AB, Canada Abstract: The clinical presentation, disease associations, and diverse treatment modalities in overcoming the challenges of managing pediatric psoriasis have been extensively summarized in this article. An extensive literature review revealed the differences in presentation of psoriasis during infancy, childhood, and adolescence. We also summarized the latest topical, systemic, and biological modalities in treating recalcitrant psoriasis. The association of psoriasis with juvenile arthritis and obesity and the significant influence of the disease on the children's quality of life were explored. The clinical presentation of psoriasis can evolve during the child's lifespan. While many treatment modalities already exist for treating pediatric psoriasis, some of the new biologics that are approved for adult patients have not been investigated in the pediatric population and no algorithm exists for their use in this population. Large clinical studies in the future will enhance our understanding with regards to their safety and potential implications in pediatric populations. Keywords: pediatric, epidemiology, juvenile arthritis, topical treatment, systemic treatment, phototherapy, biologics